Orthoplastic reconstruction of type IIIB open tibial fractures retaining debrided devitalized cortical segments: the Bristol experience 2014 to 2018. (August 2019) - Al-Hourani, K.; Stoddart, M.; Khan, U.; Riddick, A.; Kelly, M.
Abstract : Aims: Type IIIB open tibial fractures are devastating high-energy injuries. At initial debridement, the surgeon will often be faced with large bone fragments with tenuous, if any, soft-tissue attachments. Conventionally these are discarded to avoid infection. We aimed to determine if orthoplastic reconstruction using mechanically relevant devitalized bone (ORDB) was associated with an increased infection rate in type IIIB open tibial shaft fractures. Patient and Methods: This was a consecutive cohort study of 113 patients, who had sustained type IIIB fractures of the tibia following blunt trauma, over a four-year period in a level 1 trauma centre. The median age was 44.3 years (interquartile range (IQR) 28.1 to 65.9) with a median follow-up of 1.7 years (IQR 1.2 to 2.1). There were 73 male patients and 40 female patients. The primary outcome measures were deep infection rate and number of operations. The secondary outcomes were nonunion and flap failure. Results: In all, 44 patients had ORDB as part of their reconstruction, with the remaining 69 not requiring it. Eight out of 113 patients (7.1%) developed a deep infection (ORDB 1/44, non-ORDB 7/69). The median number of operations was two. A total of 16/242 complication-related reoperations were undertaken (6.6%), with 2/16 (12.5%) occurring in the ORDB group. Conclusion: In the setting of an effective orthoplastic approach to type IIIB open diaphyseal tibial fractures, using mechanically relevant debrided devitalized bone fragments in the definitive reconstruction appears to be safe. Cite this article: Bone Joint J 2019;101-B:1002–1008.